Cambio de horario y riesgo cardiovascular - Quijada R., Alonso (Revista Hospital Clínico Universidad de Chile, 2024)
The impact of light on our society is significant, influencing our central nervous system through natural light’s role in regulating circadian rhythms. Daylight Saving Time (DST) is often justified for energy savings, particularly in residential lighting. The central nervous system’s master biological clock, located in the hypothalamus, synchronizes peripheral clocks, including those in the cardiovascular system. Desynchronization between endogenous circadian systems and environmental cycles increases cardiovascular risk. The springtime DST change exacerbates social jet lag, leading to sleep debt, sympathetic activation, and increased proinflammatory cytokines. Studies show a temporary increase in myocardial infarction rates in the week following the springtime shift. From a health perspective, there’s growing evidence of negative effects on human metabolism and physiology due to changes in lighting schedules.